PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE PEER LESSON DISERTAI LKS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 13 SIJUNJUNG - Mustika, Titin; Delsi K, Delsi K; Yunita, Alfi (STKIP PGRI Sumbar, 2014)
ABSTRACTThe background of research caused less active students tend to ask your friends but the results have not been satisfactory and lack of understanding of mathematical concepts students. This study aims is to determine students mathematical concepts comprehension with peer lesson strategies and worksheets better than math concept comprehension with conventional learning. The research is experimental by using random to the experimental subject. Population is student in the class VIII SMP 13 Sijunjung. The instrument used is examinations winh reliability 0.95. To test the hypothesis used the t-test with MINITAB, obtained P-Value 0,005 less than α = 0.05, so hypothesis received. In conclusion, students mathematical concepts comprehension with peer lesson strategies and worksheets better than students math concept comprehension with conventional learning. in class VIII SMP 13 Sijunjung.